Effectiveness of Group Counseling Cognitive Restructuring Technique Model to Reduce Students' Interpersonal Communication Anxiety - Saputra, Anugrah Ragil; Japar, Muhammad; Putro, Hijrah Eko (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the effect of group counseling on cognitive restructuring techniques to reduce student interpersonal communication anxiety. This type of research is a quantitative research with a pre-experimental design research method with a one group pretest-posttest design model. The sample in this study was 15 students of FKIP Muhammadiyah University of Magelang who were taken using purposive sampling technique. The data collection tool used is a student interpersonal communication anxiety scale. Based on the results of hypothesis testing with the paired sample t-test with a significant (2-tiled) probability of 0.000 <0.05. And based on the results of the analysis and discussion, there is a difference in the average score of the student interpersonal communication anxiety scale questionnaire by 25% from the pretest results and the posttest results of the student interpersonal communication anxiety scale questionnaire.